Agronegócio canavieiro e produção de biocombustível em Frutal-MG: territorialização e impactos sociais na zona urbana - Tomaz, Rozaine Aparecida Fontes (2022)
The production of biofuels has been a viable alternative to replace fossil fuels, but this activity promotes changes in the territory, due to impacts caused by man on nature. In Brazil, one of the alternatives for the production of renewable fuels was the creation and implementation of the Program to encourage the production of ethanol, known as Proálcool (1975), which expanded both the production of alcohol fuel and stimulated the consumption of this fuel in the market. internal. The program promoted the expansion of sugar-energy industries and the resulting demands increased population displacement, which intensified changes in rural and urban territories. In this sense, this work aims to understand and describe the urban social and territorial transformations in the city of Frutal-MG, after the implementation of two sugar-energy plants, that is, Usina Frutal (Bunge group) and Usina Cerradão (Queiroz de Queiroz and Pitangueiras). The survey and description of such transformations can help in the adoption of policies by both the private and public initiatives for the development and promotion of the sugar-energy sector in the municipality in question. Therefore, a bibliographical research was carried out, through which it was possible to show that the production of sugarcane, one of the main materials for the production of biofuels, has been present in Brazil since the colonial period, when culture has already demonstrated its presence in the transformation of the territory, as well as the resulting profits. Still, it was possible to verify the expansion and relevance of this culture in the economic scenario and in the production of bioenergy. On the other hand, data from field research carried out in the municipality of Frutal/MG show that the implementation of the Usina Frutal and Usina Cerradão plants, in the last decade, promoted the expansion of the municipality, with regard to commerce, industrial, urbanism, education and housing, among other aspects, due to the expansion of capital turnover promoted by the sugar-energy sector and the economic activities related to sugarcane agribusiness in that municipality.